A Review of Phytochemical Properties and Therapeutic Activities of Glebionis coronaria - Wijaya, Evelyn Jeanette; Nathanael, Joshua; Carolan, Orlando; Adiyanto, Shakila Angjaya; Bun, Wiranata Buntaran; Sahamastuti, Agnes Anania Triavika (Indonesia International Institute for Life Sciences, 2020)
Glebionis coronaria, formerly Chrysanthemum coronarium, is one of the medicinal herbs that belong to the Asteraceae family. This review paper aims to provide information regarding the botanical description, distribution, and phytochemical properties which contribute to the medicinal properties of Glebionis coronaria. Various studies have reported the presence of tannins, vitamins, macro- and microelements, beta-carotene, carbohydrates, protein, and other bioactive compounds in the plant’s essential oil, extract, or plant parts. Researchers have uncovered the potential pharmaceutical activities of the plant, including antibacterial, antifungal, antioxidant, anti-inflammatory, anti-cholesterol, to the potential anticancer properties. Based on the scientific evidence collected, G. coronaria has the potential to be used in many clinical areas for medicinal purposes. However, appropriate clinical testing should be pursued to evaluate the medicinal effects of this plant.